(untitled) - K.V. Sarala Devi; Sulochana Sakthivel (Academia Anatomica International, 2020)
Introduction: The medial end of clavicle is connected to the upper surface of anterior end of first rib and its costal cartilage by rhomboid ligament which assist the movements of pectoral girdle as well as resist the pull of medial end of clavicle by pectoralis major and sternocleidomastiod muscles. Consequently, the attachment of it on the clavicle produces various patterns like tubercles, grooves, etc. called as the rhomboid impression. This normal variant of rhomboid impression may be interpreted sometimes as pathological lesions like necrosis, osteomyelitis, and tumour. Also, the morphology of rhomboid impression varies in different population. Such study in South Indian population is very much sparse and so this study is planned for. The objective is to it is aimed to estimate the prevalence of various morphology of rhomboid impression, to measure the anthropometry of impression and the distance from the medial end of impression to medial end of clavicle. Subjects and Methods: This descriptive study was carried in 200 adult human dry clavicles of both sides and various patterns of rhomboid impression, anteroposterior and transverse diameter of impression and distance between the medial end of impression and medial end of clavicle was measured with digital vernier caliper. Statistical analysis was done and p-value of < 0.05 is considered to be significant. Results: The most common pattern observed was depression and rough (29%) followed by elevated and rough (28.5%). The resection length of the medial end of clavicle was 11 mm from the medial end of impression to medial end of clavicle. Conclusion: The findings of the present study on the morphology and anthropometry of rhomboid impression of adult human clavicles and the resection length of medial end of rhomboid impression from the medial end of clavicle will provide guidance for the anthropologists, orthopedicians, radiologists, vascular surgeons and in forensic investigations.